Do ICT and Green Energy Policies Reduce Environmental Degradation? A Panel Analysis of Developing Nations - Basri _; Herianti (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2026)
Purpose – The issue of environmental degradation remains a pressing challenge for developing countries, hindering their efforts to achieve sustainable development. This study aims to measure the influence of energy policies, the green economy, and technological development to uncover their collective impact on environmental degradation. Method – This study uses static panel data with Fixed Effect Model (FEM) estimation and a research range of 2012-2021, involving 119 developing countries based on the World Bank. Findings – The findings reveal that renewable energy, fossil fuels, and electricity positively impact carbon emissions. Conversely, government expenditure, tax revenue, and industrial activity negatively affect carbon emissions. Additionally, green economy policies, labor intensity, the Human Development Index (HDI), and forest cover are associated with an increase in carbon emissions. Technology also exhibits a positive relationship with carbon emissions. Implications – This study underlines the importance of improving energy efficiency as a strategic step to reduce carbon emissions, while encouraging significant investment in the renewable energy sector in order to realize environmental sustainability in developing countries.Originality – This study encourages the application of the green growth model as a comprehensive global policy framework with substantial potential to reduce environmental degradation in a sustainable manner. This approach not only seeks to minimize environmental impacts but also promotes synergies between economic growth and ecosystem conservation?.